Are There Specific Benefits of Amoxicillin Plus Metronidazole in Aggregatibacter actinomycetemcomitans‐Associated Periodontitis? Double‐Masked, Randomized Clinical Trial of Efficacy and Safety. Issue 6 (1st June 2013) - Mombelli, Andrea; Cionca, Norbert; Almaghlouth, Adnan; Décaillet, Fabien; Courvoisier, Delphine S.; Giannopoulou, Catherine
Abstract : Background : It has been suggested that prescription of amoxicillin plus metronidazole in the context of periodontal therapy should be limited to patients with specific microbiologic profiles, especially those testing positive for Aggregatibacter actinomycetemcomitans . The main purpose of this analysis is to determine if patients positive for A. actinomycetemcomitans with moderate to advanced periodontitis benefit specifically from amoxicillin plus metronidazole given as an adjunct to full‐mouth scaling and root planing. Methods : This is a double‐masked, placebo‐controlled, randomized longitudinal study including 41 participants who were positive for A. actinomycetemcomitans and 41 participants who were negative for A. actinomycetemcomitans . All 82 patients received full‐mouth periodontal debridement performed within 48 hours. Patients then received either systemic antibiotics (375 mg amoxicillin and 500 mg metronidazole, three times daily) or placebo for 7 days. The primary outcome variable was persistence of sites with a probing depth (PD) >4 mm and bleeding on probing (BOP) at the 3‐month reevaluation. Using multilevel logistic regression, the effect of the antibiotics was analyzed according to the following factors (interaction effect): A. actinomycetemcomitans –positive or –negative at baseline, sex, age, smoking, tooth being a molar, and interdental location. Results : At reevaluation, participants in the test group had significantly fewer sites with a persisting PD >4 mm and BOP than control patients ( P <0.01). Being A. actinomycetemcomitans –positive or –negative did not change the effect of the antibiotics. Patients benefited from the antibiotics irrespective of sex, age, or smoking status. Molars benefited significantly more from the antibiotics than non‐molars ( P for interaction effect = 0.03). Conclusions : Patients who were positive for A. actinomycetemcomitans had no specific benefit from amoxicillin plus metronidazole. Sites on molars benefited significantly more from the antibiotics than non‐molar sites.